Architecture and mineral potential of the Paleoproterozoic Karrat Group, West Greenland - Results of the 2015 season - Rosa, D.; Guarnieri, P.; Hollis, J.; Kolb, J.; Partin, C.; Petersen, J.; Sørensen, E. V.; Thomassen, B.; Thomsen, L.; Thrane, K. (Danish Ministry of Energy, 2016)
DANMARK S OG GRØNL ANDS GEOLOGI SK E UNDERSØGE LS E R A PPORT 2016/12 (Geological Survey of Denmark and Greenland, Report 2016/12)